Efficacy and Safety of Botulinum Toxin A in Axillary Bromhidrosis and Associated Histological Changes in Sweat Glands: A Prospective Randomized Double-Blind Side-by-Side Comparison Clinical Study. Issue 12 (December 2019) - Wu, Chien-Ju; Chang, Chun-Kai; Wang, Chi-Yu; Liao, Yi-Shu; Chen, Shyi-Gen
Abstract : BACKGROUND: The efficacy of botulinum toxin A (BTX-A) therapy in axillary hyperhidrosis has been documented; however, there are a few studies reporting the efficacy of BTX-A in treating axillary bromhidrosis. The histological changes occurring in sweat glands after BTX-A treatment are also unknown. OBJECTIVE: The authors report on the efficacy and safety of BTX-A in the treatment of axillary bromhidrosis and on the histological changes in sweat glands after BTX-A treatment. MATERIALS AND METHODS: Nineteen patients were included in this study. The patients were administered BTX-A injection in one axilla and sterile normal saline as placebo in the other axilla. The degree of malodor was evaluated subjectively by the patients before and 3 months after treatment. Sweat secretion was quantified by the gravimetric method. All patients underwent standard apocrinectomy in both axillary regions. RESULTS: The mean degree of malodor and mean sweat production in the BTX-A–treated axilla were significantly lower than those in the control axilla (2.42 vs 8.00; p < .0001 and 13.33 vs 33.75 mg/min; p = .0028, respectively) at 3 months after therapy. The histological studies showed apocrine sweat glands with atrophic changes and hypoplasia in treated axilla. CONCLUSION: BTX-A injection is an easy, fast, noninvasive method of treating axillary bromhidrosis.